FONDEMENTS THÉORIQUES ET EMPIRIQUES DE L’ARTICULATION LECTURE-ÉCRITURE EN LANGUE MATERNELLE ET EN LANGUE SECONDE - Gazerani, Farzin (European Scientific Journal, ESJ, 2014)
The question of relations between reading and writing arises increasingly among didactic researchers. To better understand this issue and to shed light on the connections between these two linguistic practices, many studies are conducted. The consideration of these relations could facilitate the implementation of educational programs and improve studentsâ€™ production and comprehension in mother tongue (L1) and in a second language (L2). The objective of this study is to review various concepts related to the reading-writing connections. First, we take a historical and cultural look at reading and writing relations knowledge. Then, the connections between these two linguistic practices are studied through several educational theories in L1 and in L2. We focus, afterwards, on the profits and on the need to combine reading and writing activities. We study also how the knowledge acquired in one of these fields can be transferred to the other and what are the factors that determine this transfer process. Some empirical studies are also analyzed. Finally, students’ conceptions about the relations between reading and writing and the principles of the readingwriting combination activities are presented.